An Analysis of Accessibility to Services in Rural Areas and Structural Modeling of Factors affecting it; Case Study: Central District of Tabriz County - Mohsen Aghayari Hir; Hossein karimzadeh; nahid rahimzadeh (تحقیقات کاربردی علوم جغرافیایی)
Access, plays an important role in rural development as there is a meaningful relationship between rural development and access to infrastructure services. Villages that have less access to essential services, especially transport, faced with a lot of structural and socio-economic constraints, which are obstacles to sustainable rural development. The present study seeks to examine the accessibility and the factors affecting it. Accordingly, it is considered with descriptive-analytic research method. The statistical population of the study, consisted of villages in the central District of Tabriz County (52 villages) that there needed data were gathered from rural municipals. After validity and reliability of the research, in order to evaluate accessibility, we used the Dematel technique and ANP, then to assess the role of different elements in accessibility of rural areas, we used SEM in Amos software. Initial results of Rural Accessibility Survey showed that the Mayan Sefli village had the highest accessibility and the final result of the research are determining the role of factors in rural accessibility based on factors such as distance from the city, service centers and social status of the village are more effective than other factors in accessibility. Key words: accessibility, rural services, analytical network process, structural equation modeling, Tabriz County.